Between Fear Mongers and Samaritans: Does Information Provision Affect Attitudes towards the Right of Asylum in Germany? - Bernd Hayo; Florian Neumeier (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We utilise information experiments embedded in a representative population survey to elicit the German public's attitude towards the right of asylum. We randomly assign the interviewees to different groups and `treat' each group with different information about the asylum-seekers that came to Germany in 2015 and 2016. The treatments involve information about (i) the total number of asylum-seekers, (ii) the fiscal costs as well as (iii) the potential long-term economic benefits associated with accepting refugees, (iv) the share of Muslim asylum-seekers, and (v) the share of war refugees. We find that providing information about the fiscal costs associated with accepting refugees, and about the share of Muslim refugees, significantly increases the likelihood of opposing the right of asylum by roughly 5 and 7 percentage points, respectively. These effects are more pronounced for middle-income earners and respondents with a low level of education. Deviations of people's beliefs from the actual numbers provided by the treatments can affect their attitudes: respondents who underestimated the share of Muslim refugees are 18 percentage points more likely to call for abolishing the right of asylum when informed about the actual share.
Keywords: C90; J15; K37; Z13; 330; refugee crisis; right of asylum; immigration; perception bias; survey experiment; Germany